Polymorphisms of the murine mitochondrial ND4, CYTB and COX3 genes impact hematopoiesis during aging - Kretzschmar, Christin (Oncotarget, 2016)
During aging, mitochondrial DNA (mtDNA) can accumulate mutations leading to increasing levels of reactive oxygen species (ROS). Increased ROS were described to activate formerly quiescent hematopoietic stem cells (HSC). Mutations in mtDNA were shown to enhance the risk for myelodysplastic syndrome and leukemia. However, the complex relationship between mtDNA variations, ROS and aging of the hematopoietic system is not fully understood. Herein, three mouse strains with mtDNA polymorphisms in genes of respiratory chain complexes I (ND4), III (CYTB) and IV (COX3) were compared to a reference strain during aging. Analysis focused on ROS and ATP levels, bone marrow composition and blood counts. Additionally, hematopoietic restoration capacity following cytotoxic stress was tested. Mice with polymorphisms in ND4 and CYTB gene had significantly decreasing ROS levels in bone marrow cells during aging, without effecting ATP levels. In addition, the frequency of stem and progenitor cells increased during aging but the amount of lymphocytes in the peripheral blood decreased during aging. In summary, the presence of mtDNA polymorphisms affecting the respiratory chain complexes I, III and IV was associated with altered ROS levels as well as changes in BM and peripheral blood composition during aging.